2017
DOI: 10.1080/07373937.2017.1407940
|View full text |Cite
|
Sign up to set email alerts
|

Novel spray-dried PHA microparticles for antitumor drug release

Abstract: The production of poly-3-hydroxybutyrate and poly-3-hydroxybutyrate/polyethylene glycol-based microparticles, loaded with antitumor drugs Paclitaxel (PTX) and 5-Fluorouracil (5-FU) by spray-drying technique was investigated. The average diameter of microparticles was found to be 3.4 ± 0.5 µm and zeta potential was about-44 mV. The addition of surfactant (PEG) did not show any effect on the morphological characteristics of the particles. But the chemical structure of drug influenced on the properties. Micropart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Zeta potential for ceftriaxone-loaded MP EM and MP SD was −22:3 ± 0:6 mV and −48:0 ± 1:4 mV, respectively (compared to −17:8 ± 0:3 mV and −95:7 ± 0:6 mV for unloaded microspheres). Shershneva et al [52] reported that the average diameter of P3HB-MP SD containing paclitaxel was 3:08 ± 0:7 μm, and zeta potential was − 40:8 ± 0:9 mV, which is slightly lower than the same parameters of blank P3HB-MP SD : the average diameter was 3:36 ± 0:46 μm, and zeta potential was −44:6 ± 0:4 mV.…”
Section: Characterization Of Microparticlesmentioning
confidence: 91%
See 1 more Smart Citation
“…Zeta potential for ceftriaxone-loaded MP EM and MP SD was −22:3 ± 0:6 mV and −48:0 ± 1:4 mV, respectively (compared to −17:8 ± 0:3 mV and −95:7 ± 0:6 mV for unloaded microspheres). Shershneva et al [52] reported that the average diameter of P3HB-MP SD containing paclitaxel was 3:08 ± 0:7 μm, and zeta potential was − 40:8 ± 0:9 mV, which is slightly lower than the same parameters of blank P3HB-MP SD : the average diameter was 3:36 ± 0:46 μm, and zeta potential was −44:6 ± 0:4 mV.…”
Section: Characterization Of Microparticlesmentioning
confidence: 91%
“…These properties make PHBV more suitable in bioengineering, for obtaining particles, films, scaffolds, and surgical suture (maintaining high biocompatibility for different biological systems and complete biodegradation) [47]. Anti-inflammatory [50], antibacterial [51], antitumor [52], herbicidal [53], and other drugs have been successfully encapsulated in the PHA matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Microparticles of P3HB and P3HB were combined with polyethylene glycol(PEG) for the paclitaxel(PTX) and 5-Fluorouacil(5-FU) drugs carriage. The method showed improvement in yield and greater incorporation of drugs into microparticles, and extended release of drugs led to inhibition of tumor cell growth [75]. PHA was also utilized as an inhaled drug carrier for the lungs; however, additional research is required to determine the viability of these carriers [76].…”
Section: Drug Carriersmentioning
confidence: 99%
“…29,54 For the first time, the possibility of encapsulating an antitumor drug in a P3HB microparticle was demonstrated using the spray drying method. 55,56 The dependency of microparticle characteristics (yield. average diameter, zeta potential) on the parameters of the production process (inlet temperature, polymer solution feed rate, and polymer solution concentration) has been established.…”
Section: Introductionmentioning
confidence: 99%